A LINGUISTIC LANDSCAPE: COMPLIANCE WITH LANGUAGE PRACTICE AND POLICY IN M BLOC SPACE - Tjiawi, Lysandra Griselda (Bhumantara, 2026)
This study investigates the linguistic landscape of M Bloc Space, a prominent creative hub in Jakarta, analyzing the relationship between language policy and practice. Addressing concerns that foreign languages prevalence in Indonesian public spaces could undermine national identity, this research examines how language usage in M Bloc Space’s signage aligns with governmental regulations, specifically Law of Republic Indonesia No. 24/2009 and Presidential Decree No. 63/2019. The study utilized a mixed-methods approach, gathering primary data through direct observations (capturing photographs of public signs) and distributing questionnaires to 30 visitors aged 18-30 who live in Jakarta and Tangerang. This information was analyzed from a sociolinguistic perspective, drawing upon theories concerning multilingualism (Cenoz, 2013) and language attitude (Baker, 1995). Findings reveal a diverse linguistic landscape at M Bloc Space, with 72% of all signs being monolingual (Indonesian and English each accounting for 33%, and Japanese 6%), and 28% bilingual, predominantly Indonesian-English (19%). Public perceptions of these languages varied considerably: Indonesian signs were highly comprehensible (97% ease of understanding) and evoked strong positive sentiment (77%), consistently proving highly effective (90%). English signage also demonstrated good comprehension (74%) and positive appeal (83%), contributing to overall effectiveness (87%). Conversely, vernacular and other foreign languages presented significant comprehension barriers and less positive responses, proving less effective. Crucially, the study identifies several instances of non-compliance with national language policy, particularly purely foreign language signs and bilingual combinations omitting or downplaying Indonesian. This highlights persistent challenges in applying language regulations within vibrant, multilingual commercial settings.